Epistemologi Penyembuhan Kiai Tabib - Huda, M. Syamsul (ISLAMICA: Jurnal Studi Keislaman, 2013)
This article analyzes the epistemology of healing developed by kiai-traditional healer. In the Indonesian-Islamic tradition of healing, the kiai-traditional healer develops his own epistemological construct of healing, based on: (1) textual basis (bayÃ¢nÃ®) referring to classical Islamic references, such as al-AwfÃ¢q and Shams al-MaâÃ¢rif; (2) intuitive power (âirfÃ¢nÃ®) in the form of mystical practices, such as spiritual endeavor (mujÃ¢hadah), tawajjuh, self-cleansing (tazkÃ®yat al-nafs), waraâ, consistency (istiqÃ¢mah), and forbearance (á¹£abr); and (3) pragmatic basis of the truth, particularly its utility value for the society. Normatively, the kiai-traditional healer uses different media of healing in terms of its easiness, belief or charm. Accordingly, it results in an impression that there are many modes of healing, i.e., medical, magical, mystical, and cosmic. The meaning of healing by the kiai-traditional healer constitutes a placebo effect of well-being, that is, an attempt of the kiai to implant evocation to recover the condition of human being.